Alarme de segurança para piscina - SILVA, Adriel Beraldo da; CELTRON, Gabriel Vilela; STURARO, HEITOR; LACERDA, Lucas Henrique Costa; CASAGRANDE, Matheus Henrique Moreira (024, 2024)
Agradecemos primeiramente a Deus, pela saúde e força de vontade para a realização deste trabalho. Aos nossos familiares, especialmente aos nossos pais, que sempre foram a nossa fonte de inspiração e que investiram em nós, acreditando em nosso potencial, dando apoio para a conclusão de mais esta etapa em nossas vidas. Aos nossos companheiros, que de forma muito particular sempre estiveram ao nosso lado nos incentivando e pelo companheirismo nas horas mais difíceis. Aos nossos professores e coordenadores, pelo incentivo e todo conhecimento transmitido ao longo desses anos. Ao nosso orientador, Prof. Adalberto Zechin, por aceitar, nos orientar e contribuir com sua vasta experiência para a elaboração deste trabalho de conclusão de curso. Por fim, aos amigos que, direta ou indiretamente, fizeram parte deste sonho e que nos apoiaram e incentivaram neste período tão importante.

Accidents in domestic swimming pools, particularly involving young children, pose a significant public health concern globally, with drowning incidents frequently occurring in private pools. This project aims to develop an affordable, easy-to-install safety alarm system to enhance the security of residential pools, specifically targeting families with limited access to expensive safety technology. The proposed system utilizes ultrasonic sensors to detect movement or changes in distance in the water, triggering an audible alarm to alert individuals in the vicinity. The system is designed to be both low-cost and user-friendly, ensuring accessibility for a wide demographic, including lower-income households. The project leverages an Arduino UNO microcontroller, ultrasonic sensor (JSN-SR04T), and a solar-powered energy system to maintain the alarm's functionality. The anticipated outcome is a reduction in drowning incidents, particularly among children and pets, through the use of a simple, effective, and cost-efficient safety device. Additionally, the project addresses the social inequality in access to safety technology by providing a viable solution for families across different income levels. Through the integration of prototyping and testing, the final design demonstrates the potential to improve residential pool safety, contributing to both public health and social equity.
Keywords: Prevenção de acidentes; Sensores; Controle e Processos Industriais